Determination of moisture transport parameters of some fruits under open sun drying conditions - Togrul, Inci Tuerk; Togrul, Hasan (Taylor & Francis Inc, 2007)
In order to determine the behavior of fruits during drying under natural conditions, open sun drying experiments were conducted on apricots, grapes, peaches, figs, and plums. The drying rate curves of these fruit did not contain constant rate period, but showed a falling rate period. In the present work, Biot numbers and the mass transfer characteristics namely moisture diffusivity and moisture transfer coefficient-of selected fruits were evaluated by drying coefficients (S) and tag factors (G). The experimental results exhibited mass transfer Biot numbers in the range of 0.115-0.158, thus indicating the presence of finite internal and external resistances.
Keywords: fruits; open sun drying; biot number; moisture diffusivity; moisture transfer coefficient